2017
DOI: 10.1111/ijd.13737
|View full text |Cite
|
Sign up to set email alerts
|

Mucocutaneous manifestations in human immunodeficiency virus (HIV)‐infected patients in Nouakchott, Mauritania

Abstract: Mucocutaneous lesions occur throughout the course of HIV infection, and dermatologic findings in Mauritanian HIV-positive patients are similar to those of patients in other countries. Early detection of skin disorders in some patients may help establish the diagnosis of HIV and management of HIV-associated diseases, limiting the cost of care in low-resource countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
1
7
0
5
Order By: Relevance
“…e present research also found oral candidiasis to be a mucocutaneous disorder with significant association with low CD4 counts, which is consistent with previous studies [8,9,[21][22][23][24]. Furthermore, a statistically significant association was found between furuncle and low CD4 counts, which was compatible with Uthayakumar's research [25].Nevertheless, Ali Azfar et al could not show any association between skin manifestations and CD4 cell counts [20].…”
Section: Discussionsupporting
confidence: 92%
“…e present research also found oral candidiasis to be a mucocutaneous disorder with significant association with low CD4 counts, which is consistent with previous studies [8,9,[21][22][23][24]. Furthermore, a statistically significant association was found between furuncle and low CD4 counts, which was compatible with Uthayakumar's research [25].Nevertheless, Ali Azfar et al could not show any association between skin manifestations and CD4 cell counts [20].…”
Section: Discussionsupporting
confidence: 92%
“…Mucocutaneous manifestations are visible at any stage of human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) in patients and are often the initial manifestations of HIV/AIDS . Mucocutaneous manifestations can be used as important clues to HIV/AIDS diagnosis and can reflect the immune status in patients . CD4 cell count is an important indicator of immune status in patients, and in HIV infection, CD4 cell as an important target cell reduced gradually with illness development .…”
Section: Introductionmentioning
confidence: 99%
“…En cuanto a la relación de las manifestaciones dermatológicas y conteo de CD4 hay mayor distribución en el grupo de 200-499 cel/μL Alcivar, 11 y mayor porcentaje de dermatosis < 200 cel/μL a CV Carrillo 10 similar a nuestro estudio. El estudio de Boushab, 6 Anand, 19 demuestran que las dermatosis se encuentran en mayor proporción < 200 cel/μL CD4, que discrepan con nuestros resultados, tal vez por una muestra reducida de dichos estudios (86 y 125 casos) y por la situación geográfica localizada en Mauritania e India, respectivamente.…”
Section: Discussionunclassified
“…5 En Mauritania, África, se evaluaron 86 pacientes mayores de 18 años, en quienes se encontró que un bajo conteo de células TCD4 (< 200 células/μL) se correlacionó significativamente con la presencia de infecciones por hongos como dermatofitosis y candidiasis oral. 6 En Cuba se evaluaron 117 pacientes VIH-SIDA en quienes la dermatosis más frecuente fue de origen infeccioso: viral y micótico. 7 En Ecuador en el periodo comprendido entre 1984-2010 se detalló una cifra de 18,739 casos confirmados de infección por el VIH.…”
Section: Wwwmedigraphicorgmxunclassified